Biologically effective solar ultraviolet exposures and the potential skin cancer risk for individual gold medalists of the 2020 Tokyo Summer Olympic Games. Issue 1 (2nd January 2020) - Downs, Nathan J.; Axelsen, Taryn; Schouten, Peter; Igoe, Damien, P.; Parisi, Alfio, V.; Vanos, Jennifer
ABSTRACT: Personal solar ultraviolet radiation exposure models were developed for 144 Olympic events scheduled outdoors from across the 33 sport disciplines that will compete in Tokyo between 24 July and 9 August 2020. Ambient exposure models were developed from existing atmospheric parameters measured over Tokyo (35.7°N 139.7°E) and were used to weight erythemally effective solar ultraviolet exposure to gold medalists, taking into account body posture and expected protection by competitor's clothing which was assessed in comparison to respective medalists of the 2016 Rio Olympics. Individual exposure models consider the ultraviolet surface albedo (lawn, concrete, water or sand) and timing of daily events held within Olympic venues. Exposure assessments are presented, including assessments of all preliminary rounds and qualifiers. Within scheduled outdoor events, we award first place (representing the highest and most harmful UV exposure) to the women's tennis singles (1680 J/m 2 ), second to men's golf (1530 J/m 2 ) and third to the men's cycling road race (941 J/m 2 ) for the highest expected erythemally effective solar ultraviolet radiation exposures of the 2020 Tokyo Games. The highest expected solar ultraviolet exposures for nations expected to win greater than three gold medals among the outdoor events were found to occur in athletes from Kenya followed closely by the United States and Hungary. Gold medalists from South Korea were found to demonstrate the highest level of sun protection due to clothing at the 2016 Rio Games, and are thus expected to receive the greatest relative reduction in erythemally effective exposure during the 2020 Tokyo Games.